Innovations in Primary School Teacher Education: Improving the Quality of Learning in the Digital Era - Fitri Meilana, Septi (Zona Education Indonesia, 2024)
This research aims to explore innovations in elementary school teacher education based on digital technology and its impact on learning quality. Using a qualitative descriptive approach and case study design, this study involves several elementary schools that have implemented digital technology in the learning process. Data were collected through in-depth interviews, participatory observations, and documentation analysis. The results of the study show that the application of digital technology can increase student engagement, teaching creativity, and teachers' digital competence. Nonetheless, challenges such as infrastructure limitations and technology access gaps have also been identified. These findings underscore the importance of ongoing support for teachers and investment in technology infrastructure to maximize the benefits of digital innovation in education